Writing and heritage in contemporary Spain the imaginary museum of literature - Davis, Stuart 1975- (Boydell & Brewer, 2012)
This is an innovative exploration of cultural heritage and the literary traditions that shape the contemporary literary scene in Spain. Through a coalescence of museum studies, metacriticism and traditional literary criticism the study interweaves discussion of museum spaces with literary analysis, exploring them as agents of memorialisation and a means for preserving and conveying heritage. Following introductory explorations of the development of museums and the literary canon, each chapter begins with a "visit" to a Spanish museum, establishing the framework for the subsequent discussion of critical practices and texts. Case studies include examination of the palimpsest and unconscious influence of canonical cores; the response to masculine traditions of poetry and art; counter-culture of the 1990s; and the ethical concerns of postmemory writing. STUART DAVIS is a Lecturer in Spanish, Girton College, and Newton Trust Lecturer in the Department of Spanish and Portuguese, University of Cambridge